1995
DOI: 10.1177/43.4.7897181
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization analyses of Na, K-ATPase alpha-subunit expression during early larval development of Artemia franciscana.

Abstract: (4A3444).The spatial pattern of expression of the mRNA encoded by the Na,K-ATPase a-subunit cDNA done pArATNal36 was determined by in situ hybridization of fm, second, and third instar Artma fianuscaaa larvae. This mRNA was expresed at high levels in the salt gland, the antennal gland, and the end of the midgut, which are the three main osmoregulatory organs in Artema at these stages of development. The pattem of expression was similar at the three stages of development analyzed, although the level of expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…,K ? )-ATPase activity have been undertaken mainly using crude tissue homogenates (Conte et al 1977;Sun et al 1991;Lee and Watts 1994;Escalante et al 1995;Wilder et al 2001;Huong et al 2004;Ituarte et al 2008) and not isolated microsomal fractions as employed here, and direct comparison is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…,K ? )-ATPase activity have been undertaken mainly using crude tissue homogenates (Conte et al 1977;Sun et al 1991;Lee and Watts 1994;Escalante et al 1995;Wilder et al 2001;Huong et al 2004;Ituarte et al 2008) and not isolated microsomal fractions as employed here, and direct comparison is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…The larval stages have been neglected (Read 1984;Charmantier 1998;Haond et al 1999;Khodabandeh et al 2006) due to their small dimensions and reduced hemolymph volume (Charmantier 1998;Anger 2003;Augusto et al 2007). The few studies that do correlate the salinity tolerance of early ontogenetic stages with their osmoregulatory capabilities have been hampered by a lack of information on the kinetic characteristics of the transporters involved in osmoregulation during larval development (Conte et al 1977;Read 1984;Sun et al 1991;Lee and Watts 1994;Escalante et al 1995;Augusto et al 2007;Ituarte et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Artemia, in situ hybridization experiments have shown that one of the α subunit clones, named pArATNa136, is expressed in the main larval osmoregulatory organs, salt gland, antennal gland and midgut, suggesting that the encoded protein plays an important role in salt tolerance [19]. This cDNA has been proposed to code for the α1 protein isoform because their tissue specificity and temporal pattern of expression during development are coincident.…”
Section: Introductionmentioning
confidence: 99%
“…This cDNA has been proposed to code for the α1 protein isoform because their tissue specificity and temporal pattern of expression during development are coincident. For similar reasons, the other identified cDNA clone, which is specifically expressed in the salt gland, has been proposed to code for the α2 protein isoform [20], although there are some discrepancies between patterns of expression of the protein and mRNA [19].…”
Section: Introductionmentioning
confidence: 99%
“…5 mM EDTA, pH 8.0, for 5 min. washed in PBS for 5 min, fixed with 4 % paraformaldehyde in PBS for 20 min at RT, and washed three times in PBS for 10 min at R I The conditions used for in situ hybridization were the same as described by Escalante et al (1995), using antidigoxigenin antibodies coupled to alkaline phosphatase (Boehringer Mannheim). DNA from the plasmid vector pUC18 was used as probe in negative control hybridization experiments.…”
Section: Introductionmentioning
confidence: 99%